Implementation Of the Independent Curriculum In the Subject Of Aqidah Akhlak At MTS Nur Iman Sleman - Lidinilah, Izul Haq; Achadi, Muhammad Wasith (Institut Agama Islam Negeri (IAIN) Bone, 2024)
That the independent curriculum is a rule in the implementation of education in Indonesia, the presence of the independent curriculum is also a form of evaluation of the 2013 curriculum, this is a means of relevance to current developments. The study of Moral Aqidah is interpreted as a mandatory subject for Madrasahs. The meaning of the moral aqidah itself is that Aqidah is defined as a belief that is believed by the human heart, while morals are a reflection of the human character itself. So this lesson aims to shape the character of students who have strong faith and noble character.The implementation of the independent curriculum in the Aqidah Aklak subject at MA Nur Iman goes through various stages: first is planning, this stage plans everything that will be done such as learning strategies, facilities used and others, second is implementation, this stage is the core of the implementation, the plan that has been In this stage it is implemented, the last is evaluation, here everything that has been done must be evaluated so that in the future it will be even better.